Enzyme‐Assisted Cyclic Signal Amplification by Using Carbon Nanomaterials for Hg2+ Detection. Issue 14 (15th April 2020) - Liu, Wei; Yang, Lijuan; Yu, Kaili; Li, Yongyang
Abstract: A novel and simple fluorescence method for Hg 2+ recognition and detection has been developed based on T‐Hg 2+ ‐T complex and exonuclease III (Exo III) assisted cyclic signal amplification. Graphene oxide (GO) and carbon nanotubes (CNTs) were used to quench the fluorescence FAM‐labelled single strand DNA (FAM‐ssDNA). The optimum conditions, including GO and CNTs concentrations, enzyme concentration and enzymatic hydrolysis time, were studied. The linear range, regression equation and metal ion selectivity were further studied and compared. The recovery rates of Hg 2+ in tap water and urine were between 93.83–103.5%. Abstract : A novel and simple fluorescence method for Hg 2+ recognition and detection has been developed based on T‐Hg 2+ ‐T complex and exonuclease III (Exo III) assisted cyclic signal amplification. The fluorescence of FAM‐labelled single strand DNA (FAM‐ssDNA) was quenched by carbon nanomaterials. After adding Hg 2+ and Exo III, the formed double helix DNAand/or hairpin structures were splited and the fluorescence were recovered and amplified.